Nutritional status of Lotus corniculatus L. in Uruguay - Barbazán, M.; Ferrando, M.; Zamalvide, J. (Agrociencia Uruguay, 2007)
The information available at national and world-wide level on nutritional requirements of Lotus corniculatus L. is little. For that reason, the objectives of this work were to know the concentrations nutrients of this culture in Uruguay, to detect situations with greater probability of deficiencies, and to establish relations with characteristics of the soils. During three years a nutritional survey of Lotus was conducted, collecting soil and plant samples of 179 commercial fields widely distributed around the country. The ranges of concentrations of macronutrients in plant were: 1.51 - 4.15% N; 0.11 - 0.38% P; 0.81 - 3.30% K; 0.34 - 1.84% Ca; 0.18 - 0.59% Mg; and 0.12 - 0.36% S, and those of micronutrients were: 4 - 58; 39 - 350; 31 - 207, and 12 - 115 mg kg-1 of Cu, Fe, Mn, and Zn, respectively. The more frequently deficient nutrients were P, S, and K, with 72, 16, and 14% of the fields with concentrations of P, S, and K in plant lower than those of the critical concentrations. The high frequency of P as limiting nutrient suggests the necessity of improving P fertilization management. The differences observed in S, are explained by the processes of gain and loss of the soil organic matter. In some soils on Formation Tacuarembó, Cretácico, Planicies y lomadas del Este, or Basalto, could occur K responses. In soils rich in K or poor in Mg (Formation Fray Bentos), Mg concentrations in plant were the lowest. There were not evidences that other nutrients could be limiting productivity of Lotus in Uruguay.